2021
DOI: 10.1007/s12187-021-09886-1
|View full text |Cite
|
Sign up to set email alerts
|

Life Satisfaction and Character Strenghs in Ecuatorian Adolescents

Abstract: There is empirical evidence that life satisfaction (LS) in adolescence is associated with adequate development and future well-being. Research into the factors underpinning LS can therefore help to promote healthier development of societies. The aim of this study was to extend knowledge about LS among adolescents in Ecuador, a Latin American country for which research on this topic is lacking. Specifically, we analyze the relationship between LS and character strengths, controlling for gender, age, socioeconom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 81 publications
1
2
0
Order By: Relevance
“… 29 Hope is an action-oriented strength, as it implies motivation and confidence that desired goals can be achieved. Our findings here are consistent with previous research in different populations showing that hope is positively related to life satisfaction, well-being, 33 , 35 , 37 happiness, 28 , 29 , 48 physical and mental health, 53 and quality of life, 54 and also that it mitigates the negative consequences of trauma and stress. 55 In women with breast cancer, higher levels of hope have been linked to better quality of life 56 and lower levels of perceived stress.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“… 29 Hope is an action-oriented strength, as it implies motivation and confidence that desired goals can be achieved. Our findings here are consistent with previous research in different populations showing that hope is positively related to life satisfaction, well-being, 33 , 35 , 37 happiness, 28 , 29 , 48 physical and mental health, 53 and quality of life, 54 and also that it mitigates the negative consequences of trauma and stress. 55 In women with breast cancer, higher levels of hope have been linked to better quality of life 56 and lower levels of perceived stress.…”
Section: Discussionsupporting
confidence: 93%
“…34,35 Research with adolescents has observed a similar relationship between hope and life satisfaction. 31,33,36,37 In people with physical illness, higher levels of zest, hope, and leadership were found to be related to fewer problems of depression and anxiety, whereas bravery, humor, and kindness were associated with the recovery of satisfaction with life. 38 Regarding women with breast cancer, studies analyzing the association between character strengths and life satisfaction are scarce.…”
mentioning
confidence: 99%
See 1 more Smart Citation